Significant haematuria caused by a pseudo-aneurysm in nephroblastoma - Jaques van Heerden; Hansraj Mangray; Fernando Ghimenton; Deneys Reitz (Elsevier, 2019)
A 7-year-old boy presented with a nephroblastoma, frank haematuria and hypovolemic shock. The haemorrhage was controlled with embolization of the right renal artery and followed by a nephrectomy. In paediatric oncology, interventional radiology has limited application beyond specific indications. This case describes a rare complication where embolization was the key to successful treatment. Keywords: Haematuria, Pseudo-aneurysm, Nephroblastoma